Pre-DUS screening of elite maize inbreds via SSR markers and ideotype selection - RAKA FAUZI MITREKA; ERLANGGA DWI ATMOJO; SHANASYA NAJWA DEVYA ASYARI; AZERI GAUTAMA ARIFIN; DARMAWAN SAPTADI; ARIFIN NOOR SUGIHARTO (Society for Indonesian Biodiversity, 2026)
Abstract. Mitreka RF, Atmojo ED, Asyari SND, Arifin AG, Saptadi D, Sugiharto AN. 2026. Pre-DUS screening of elite maize inbreds via SSR markers and ideotype selection. Biodiversitas 27 (4): d270433. https://doi.org/10.13057/biodiv/d270433. Maize is a key cereal crop in Indonesia, but traditional pre-DUS evaluation relies heavily on morphological traits, which are often confounded by environmental influences. This limitation hinders precise genetic differentiation and efficient selection of elite inbred lines. This study aimed to support pre-DUS differentiation by integrating Simple Sequence Repeat markers with quantitative phenotypic traits and multivariate selection. Twelve elite maize inbred lines were evaluated under field conditions using a randomized complete block design; nine quantitative traits were recorded, and 10 SSR markers were used for genotyping. Our findings present three parallel outputs: phenotypic performance, molecular characterization, and multivariate selection outcomes. Phenotypically, integrated analysis revealed significant variation, with JUNRT1 and JUNRT3 demonstrating superior performance in key yield components (kernel weight, ear diameter, dehusked ear weight, and potential yield) alongside earlier flowering. Molecularly, SSR markers provided evidence consistent with genetic differentiation and predominantly single-fragment patterns in bulked SSR profiles for JUNRT1 and JUNRT3, complementing phenotypic data for pre-DUS characterization. Through multivariate analysis, Factor Analysis effectively reduced nine quantitative traits into three meaningful components: flowering time, yield components, and ear/kernel attributes. Subsequently, the Multi-Trait Genotype-Ideotype Distance Index simultaneously favored early maturity and high yield components, ranking JUNRT1 and JUNRT3 among the top lines. Collectively, this integrated morpho-molecular workflow provides screening-level evidence for pre-DUS characterization and prioritization of candidate parents for subsequent multi-location testing and potential hybrid development. It is crucial to reiterate that these outcomes are intended to support, not replace, formal DUS testing. However, single location-season phenotyping and bulked SSR profiles cannot confirm uniformity or stability under formal DUS requirements.